Renoprotective effects of zinc sulfate against transient liver ischemia/reperfusion injury in rats - Izadpanah Gheitasi; Amir Hossein Doustimotlagh; Esmaeel Panahi Kokhdan; Ghaidafeh Akbari; Mehrzad Jafari Barmak (Heliyon, 2023)
Objectives: Liver ischemia/reperfusion damage frequently occurs in setting of hepatic resection and liver transplantation. It leads to disturbance in remote organs such as heart, lung and kidneys. This study explored the consequences of hepatic ischemia/reperfusion on the oxidative stress parameters, biochemical factors, and histopathological alterations in the kidney's rats, as well as evaluated the role of zinc sulfate on above-mentioned parameters. Materials and methods: Twenty-eight male Wistar rats were accidently assigned into four groups (n = 7). They were Sham, ischemia/reperfusion, zinc sulfate pretreatment, and zinc sulfate pretreatment + ischemia/reperfusion groups. Sham group: obtained normal saline (2 ml/day, seven consecutive days), intraperitoneally, zinc sulfate pretreatment group: obtained zinc sulfate (5 mg/kg, seven consecutive days, intraperitoneally). Ischemia/reperfusion group: obtained normal saline as mentioned previous, then rats experienced the partial ischemia (%70) for 45 min followed by 60 min reperfusion. Zinc sulfate pretreatment group: obtained zinc sulfate as mentioned previous, then rats experience the partial ischemia/reperfusion as presented earlier. At the end of investigation, blood was withdrawn, liver and renal tissues were removed. Then, biochemical and oxidative stress parameters, and histological changes were evaluated in the mentioned tissues. Results: The findings of this experiment indicated that zinc sulfate markedly reduced the serum levels of liver and kidney function tests in relative to ischemia/reperfusion group. Also, antioxidant enzymes activity, ferric reducing antioxidant power, and nitric oxide significantly increased, while malondialdehyde level declined in the renal tissue of zinc sulfate + ischemia/reperfusion group compared to ischemia/reperfusion rats. Furthermore, zinc sulfate alleviated the liver and kidneys histopathological alterations following ischemia/reperfusion. Conclusion: Zinc sulfate ameliorated liver and kidney function, and improved oxidant-antioxidant balance in favor of antioxidants. It is suggested that zinc sulfate may be beneficial effects on hepato-renal injury after ischemia/reperfusion.